A fast solar architecture design method towards zero heating energy: A SHF-SLR-based model and its parameters. (1st November 2022) - Meng, Xiangxin; Liu, Yan; Wang, Shangyu; Chen, Feiyu; Cao, Qimeng; Yang, Liu
Abstract: Accurate predictions of the performance of zero heating energy buildings (ZHEBs) are essential for achieving the final goal of zero energy buildings due to the large share. Therefore, developing a fast method for the designer, especially architects to assess ZHEBs is becoming increasingly important using basic building design parameters. The present study established the solar heating fraction (SHF)–solar load rate (SLR)–based model, using 1042 meteorological data measurements and 48 typical buildings. With the model, the correlations between the SLR and shape factor (SF) to meet the requirements for ZHEBs (SHF = 1) were established. The equation was evaluated based on the mean absolute percentage error and Pearson's correlation coefficient. The results showed that the SLR–SF equation could fast evaluate the building meets for ZHEB, and the SLR was negatively correlated with SF under known window-to-wall ratio (WWR), Length-to-width ratio (LWR), and floor height. Optimal schemes of building design parameters were obtained for building floor heights ≥4, LWR1: SF ≤ 0.25, LWR2: SF ≤ 0.23, LWR3: SF ≤ 0.27, LWR4: SF ≤ 0.29, and with building floor heights ≤3, LWR1: SF ≤ 0.50, LWR2: SF ≤ 0.54, LWR3: SF ≤ 0.54, LWR4: SF ≤ 0.57. The result provided basic line to achieve ZHEBs, even zero energy buildings, especially in areas with rich solar energy in winter. Highlights: Relationship between solar heating fraction (SHF) and solar load ratio (SLR). SHF–SLR–based model proposed to assess zero heating energy buildings (ZHEBs). Relationship obtained between shape factor and SLR to meet requirements for ZHEBs. Optimal schemes of building design parameters toward ZHEBs were obtained.